Feeding dairy cows at Shika Agricultural Research Station - Koch, B.A.; Gambo, A. (1971)
Results of feeding trials conducted at Shika agricultural research station in Nigeria were reported. The study was carried out to assess the genetic potential of dairy cows and to determine feed costs for milk production under urban dairy conditions. Comparisons of production performance on zea mays silage to pennisetum purpureum silage and improved pasture to unimproved pasture are included.